Consumer Protection in the Digital Era: An Analysis of Consumer Protection in E-Commerce - Ismawati; Suud Sarim Karimullah (Islamic Research Publiser, 2024)
The digital revolution has fundamentally reshaped the way consumers interact with the marketplace. The emergence of e-commerce platforms has accelerated economic transactions while simultaneously introducing complex legal challenges, particularly regarding consumer protection. This study critically examines the effectiveness of consumer protection mechanisms in the digital era, with a focus on e-commerce practices in both domestic and cross-border contexts. Using a normative, juridical, and qualitative approach, the research examines the implementation of consumer protection principles in online transactions, with a specific focus on transparency, data privacy, unfair contract terms, and the accessibility of dispute resolution channels. The findings indicate that although several legal frameworks—such as electronic transaction laws and consumer protection statutes—have adapted to digital developments, their enforcement remains inconsistent and fragmented. Many consumers are unaware of their rights in digital transactions, while existing regulations often struggle to keep pace with the rapid pace of technological innovation. The study also reveals that dispute resolution in e-commerce is still dominated by platform-based mechanisms, which tend to prioritize business interests over consumer rights. Furthermore, cross-border transactions often create jurisdictional ambiguities that weaken consumer protection. This research makes an academic contribution by presenting a conceptual model of adaptive consumer protection, which integrates technological responsiveness, legal flexibility, and ethical accountability. It extends the theoretical discourse on digital consumer law by proposing the harmonization of international standards and the establishment of collaborative enforcement mechanisms between states and digital platforms.